Preventing the scars of neonatal intensive care. Issue 1 (January 1994) - Davies, J; Gault, D; Buchdahl, R
Abstract : Two cases are reported of serious extravasation injuries due to parenteral nutrition in infants born at 24 and 28 weeks' gestation. Major scarring and the need for plastic surgery were prevented by using a technique of subcutaneous hyaluronidase and saline flushing.